Pelembagaan Regional mengenai Hak Asasi Manusia di ASEAN - Madu, Ludiro (Jurnal Hubungan Internasional, 2016)
Institutionalization of non-traditional issues has become new phenomenon for ASEAN, including those related to human rights in the form of ASEAN Intergovernmental Commission on Human Rights (AICHR). While its instutionalization has been one of ASEAN’s achievements for its sensitive characters, the AICHR also revealed several complexities. The first problem is related to ASEAN’s further attempts for boosting regional cooperation on human rights among its member states. Diversified political system of ASEAN’s states is deemed as its obstacle. The second refers to regional architecture of ASEAN which is prone to be loosely structured and more focussed on economic development and regional political stability. This paper seeks to explain dynamics among ASEAN’s member states in institutionalizing human rights issues. AICHR has been one of the most successful ASEAN’s achievements in managing non-traditional issues and promoting participation of non-state actors in this region. In doing so, this paper also shows tug-of-war between regional and national interests in the process of formulating regional regime on human rights in ASEAN.